Amino acid sensing and assimilation by the fungal pathogen candida albicans in the human host - Silao, FGS; Ljungdahl, PO (MDPI, 2021)
Nutrient uptake is essential for cellular life and the capacity to perceive extracellular nutrients is critical for coordinating their uptake and metabolism. Commensal fungal pathogens, e.g., Candida albicans, have evolved in close association with human hosts and are well-adapted to using diverse nutrients found in discrete host niches. Human cells that cannot synthesize all amino acids require the uptake of the "essential amino acids" to remain viable. Consistently, high levels of amino acids circulate in the blood. Host proteins are rich sources of amino acids but their use depends on proteases to cleave them into smaller peptides and free amino acids. C. albicans responds to extracellular amino acids by pleiotropically enhancing their uptake and derive energy from their catabolism to power opportunistic virulent growth. Studies using Saccharomyces cerevisiae have established paradigms to understand metabolic processes in C. albicans; however, fundamental differences exist. The advent of CRISPR/Cas9-based methods facilitate genetic analysis in C. albicans, and state-of-the-art molecular biological techniques are being applied to directly examine growth requirements in vivo and in situ in infected hosts. The combination of divergent approaches can illuminate the biological roles of individual cellular components. Here we discuss recent findings regarding nutrient sensing with a focus on amino acid uptake and metabolism, processes that underlie the virulence of C. albicans.